Interspecies virus transfer via protoplast fusions between Fusarium poae and black Aspergillus strains - A D van Diepeningen; A J M Debets; S M Slakhorst; C Fekete; L Hornok; R F Hoekstra (Fungal Genetics Reports, 2000)
Similarities between the genome organisation of dsRNA mycoviruses and dsRNA patterns in different fungal species suggest a relatedness between these viruses, which could be the result of co-evolved infections or of interspecies transfer. Such interspecies transfer between species is suggested by our observation of transfer and maintenance of mycoviral dsRNAs between Fusarium and Aspergillus via protoplast fusion.